Open reduction of carpometacarpal fracture dislocations: a case report - Singh, Surya Vijay; Puri, Gyanendra; Chopra, Rajesh K.; Kuppusamy, Nivendiran; Samanta, Pritam; Goel, Lakshay (International Journal of Research in Orthopaedics, 2019)
Dislocations of the carpometacarpal (CMC) joints are uncommon injuries. Up to 70% of carpometacarpal dislocations are missed or misdiagnosed. Post traumatic dislocation of carpal and CMC joint results most commonly due to high energy trauma. A 24 year old male with right hand dominant presented 5 days after in emergency room with alleged history of fall from 4 feet height on right hand with wrist in extension. On clinical examination revealed marked swelling over dorsum of right hand with wound over volar aspect of hand. There was minimal movement of fingers due to pain. There was no finger paresthesia. CRT was normal. Radiography revealed a volar dislocation of 2nd to 5th CMC joint with intra-articular fracture of base of proximal phalanx of the thumb. He was treated by open reduction and percutaneous fixation using Kirschner wires. The functional results were excellent at 6 months of follow-up.